ANALISIS USABILITY PADA PLATFORM GREDU BELAJAR DI SEKOLAH MENENGAH KEJURUAN NEGERI 1 SAYUNG DEMAK - Billah, Muayyad; Farkhan, Mukhamad; Ardiyanto, Wahyu Indra; Ristanto, Riska Dami (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2023)
GREDU Learning is a web-based learning platform and application that provides features to be able to upload and access assignments in the form of files, images and videos regarding learning to students related to the material to be studied. Usability is an aspect that can be used as a basis for measuring the level of success regarding the implementation of a platform or device system to achieve goals. The research method used is Usability testing using the USE Questionnaire. USE Questionnaire is a questionnaire that is used to measure usability consisting of, efficiency, effectiveness and level of satisfaction. This test was carried out using the ADDIE method and based on the USE Questionnaire with the 4 aspects used in the USE Questionnaire, namely Ease of Use, Ease of Learning, Satisfaction and Usefulness. The purpose of this study was to determine the level of use of the GREDU Learning platform for students. Based on the results of the analysis, the total percentage value is 76.08%. So it can be concluded that the use of the GREDU Learning platform is feasible and can be used as a learning platform.